Colonialism and Cultural Change in Indonesia (Journal Of Natural Sciences And Multidisciplinary research, 2026)
This article discusses the entry and development of European cultural influences in Indonesia from the arrival of the Portuguese to the Dutch colonial period and its impact on social and cultural changes. The expansion of Europe driven by economic, political, and religious interests brought about changes in the fields of trade, administration, education, art, and culture. However, the people of the archipelago do not accept these influences passively, but respond to them through the process of acculturation. This process gave birth to the Indis culture as a form of mixing European and local cultures reflected in architecture, lifestyle, art, traditions, and culinary. This article emphasizes that the colonial cultural heritage in Indonesia is the result of cultural interaction and negotiation that forms Indonesia's multicultural identity.